Convenient Cyanation of Diazonium Tetrafluoroborate Salt Toward Firefly Luciferin Precursors. (26th May 2020) - Shahmoradi, Ghasem; Amani, Saeid
ABSTRACT: In this paper, the high-yielding synthesis of 2-cyano-6-methoxybenzothiazole and 2-cyano-6-hydroxybenzothiazole through catalytic Sandmeyer cyanation was described. In this Sandmeyer type reaction, 2-amino-6-methoxybenzo-thiazole and 2-amino-6-hydroxybenzothiazole were converted to the corresponding diazonium tetrafluoroborate salt and subsequently cyanated in the presence of Cu(I)/Cu(II)/ N, N, N′, N′-tetramethyl ethylenediamine as a catalyst. This protocol features mild reaction conditions, high yielding, short reaction time and capability for large-scale synthesis. In addition, a direct, more efficient and economical approach for 2-cyano-6-hydroxybenzothiazole was presented.